Kompetensi dan Motivasi terhadap Kinerja Pegawai pada Dinas Pendidikan dan Kebudayaan - Rudi Eduar (IPM2KPE, 2021)
This study aims to determine the effect of competence, motivation, and the influence of both on the performance of the Department of Education and Culture employees. This type of research is quantitative with multiple linear regression analysis, T-test, and F test. The equation Y=29,821+0,064+0,180 obtained the results. The T-test results showed that the t-count of competence (X₁) was 0.481 with a significant level of 0.632, and the motivational t-count value (X₂) was 1.572 with a significant level of 0.000. F test results obtained 1.298 by taking a significant level of 0.05 than with a significant level of 0.000. The conclusions obtained are as follows, a) Competition has no significant effect on employee performance; b) Motivation shows a significant effect on employee performance; c) Simultaneously competition and motivation affect employee performance. Keywords: Performance, Competency, Motivation